Rachela Bojmwoł. Szkic do portretu - Kisiel, Marian (Rusycystyczne Studia Literaturoznawcze, 2017)
The paper delineates the history of Rachel Boymvol — a poetess, and an author of aphorisms, fables both for children and adults, and a compendium concerning Yiddish idiomatics. Her life — from the fascination with communism in the 1930s to facing persecutions in 1940s and 1950s, and emigration to Israel in 1971 — is one of the many fates of Russian writers of Jewish descent. Previously a noteworthy fabulist, published in millions of volumes, this later forgotten author is slowly regaining her place within Russian literature after 2000.